Efficiency of Implementation of Alternative Dispute Settlement for Fintech Lending Users (Universitas Negeri Semarang, 2022)
This article aims to analyze the dispute resolution mechanism at PT Satustop Finansial Solusi and the effective and efficient application of APS for fintech lending users. This article includes a type of normative legal research that is prescriptive and applied with a legal approach, a case approach, and a conceptual approach. Source materials obtained through primary legal materials and secondary legal materials. The technique used is the syllogism method through a deductive mindset. The dispute resolution mechanism applied by PT Satustop Finansial Solusi is through litigation (judicial institutions). The results show that dispute resolution through litigation is deemed less effective and efficient, so the authors use the provisions in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, POJK Number 1/POJK.07/2014 concerning Alternative Dispute Resolution Institutions in the Financial Services Sector, and the Theory of Economic Analysis of Law proposed by Richard A. Posner. In this theory, states that the application of economic principles as rational choices to analyze legal issues.